1994
DOI: 10.1128/mcb.14.6.3577
|View full text |Cite
|
Sign up to set email alerts
|

Role of IRS-1-GRB-2 complexes in insulin signaling.

Abstract: GRB-2 is a small S112-and SH3 domain-containing adapter protein that associates with the mammalian SOS homolog to regulate p2l1 during growth factor signaling. During insulin stimulation, GRB-2 binds to the phosphorylated Y895VNI motif of IRS-1. Substitution of Tyr-895 with phenylalanine (IRS-1F-895) prevented the IRS-1-GRB-2 association in vivo and in vitro. The myeloid progenitor cell line, 32-D, is insensitive to insulin because it contains few insulin receptors and no IRS-i. Coexpression of IRS-1 or IRS-1F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(146 citation statements)
references
References 46 publications
6
139
0
1
Order By: Relevance
“…We looked at the effect of RA on phosphorylation of the p44 and p42 (erk1 and erk2) members of the MAPK pathway and phosphorylation of AKT, a serine/threonine kinase activated downstream of PI 3-kinase. Phosphorylated IRS-1 can activate erk1 and erk2 by binding Grb2 and activating the ras/MAPK pathway (Myers et al, 1994). In spite of decreased levels of phosphorylated IRS-1, we found that The effects of RA on the serine phosphorylation status of AKT kinase were not due to a change in the level of total AKT (Figure 4c).…”
Section: Ra Impairs Igf-i-stimulated Akt Activity But Not Erk1/ 2 Actmentioning
confidence: 62%
“…We looked at the effect of RA on phosphorylation of the p44 and p42 (erk1 and erk2) members of the MAPK pathway and phosphorylation of AKT, a serine/threonine kinase activated downstream of PI 3-kinase. Phosphorylated IRS-1 can activate erk1 and erk2 by binding Grb2 and activating the ras/MAPK pathway (Myers et al, 1994). In spite of decreased levels of phosphorylated IRS-1, we found that The effects of RA on the serine phosphorylation status of AKT kinase were not due to a change in the level of total AKT (Figure 4c).…”
Section: Ra Impairs Igf-i-stimulated Akt Activity But Not Erk1/ 2 Actmentioning
confidence: 62%
“…MAP kinases are activated by dual-specificity MAP kinase kinases that phosphorylate adjacent tyrosine and threonine residues (29). During insulin stimulation, ERK1 and ERK2 are strongly activated by the dualspecificity kinases MEK1 or MEK2, which are activated when Grb2/Sos bound to Irs1 or Shc activates the Ras 3 Raf cascade (53,54); however, a molecular pathway linking the receptors for proinflammatory cytokines or insulin to JNK is difficult to establish.…”
Section: Discussionmentioning
confidence: 99%
“…32D cells expressing transfected IRS proteins were as described (51,52) and maintained in medium containing 5-10 mM histidinol (Sigma).…”
Section: Methodsmentioning
confidence: 99%